Discrete Element Modeling of Southeast Asia's 3D Lithospheric Deformation During the Indian Collision. Issue 1 (25th January 2023) - Jiao, Liqing; Tapponnier, Paul; Donzé, Frédéric‐Victor; Scholtès, Luc; Gaudemer, Yves; Xu, Xiwei
Abstract: The Indian collision has deformed the eastern Asian continent in a multifaceted way, uplifting Tibet and surrounding mountains, activating ≥1, 000 km‐long strike‐slip faults, and opening Tertiary rifts and oceanic basins up to ≈3, 000 km away from the Himalayas. Modeling such broad‐scale tectonics has been challenging. While continent‐scale, lithospheric deformation appears to have been primarily taken‐up by long, narrow, inter‐connected shear‐zones with large offsets, the contribution of processes such as channel‐flow, collapse, delamination, etc… has remained contentious. Here, based on increasing 4 G (Geological, Geophysical, Geochronological, Geodetic) evidence including kinematic and timing constraints on the main mechanisms at play, we use Discrete Element (DE) Modeling to simulate and further understand the evolution of 3D strain across east Asia since the onset of collision, ≈55 Ma ago. The planar, 50 million km 2, 125 km‐thick models are scaled for gravity. The approach permits mega‐fault generation and evolution without pre‐arranged initial settings. The results provide insight into fault birth, propagation and motion, as well as mountain building and plateau growth. They corroborate that continental crustal thickening across Tibet alternated with the extrusion of large blocks that rifted apart in the far field. Remarkably, without changes in boundary conditions or indentation rate, the DE model also vindicates slip reversal along initial strike‐slip shear zones. Plain Language Summary: To better understand the Tertiary, three‐dimensional tectonics of South‐Eastern Asia, mostly a result of the north‐eastwards penetration of "rigid" India since ≈55 Ma, we use a Discrete Element Modeling approach. The technique permits the generation and evolution of large faults without initial pre‐setting. The model results substantiate the northwards growth of 4/5 Tibet sub‐plateaus, atop south‐dipping, subducted lithospheric slabs. Two long strike‐slip faults, comparable to the Ailao‐Shan‐Red River and Altyn Tagh‐Haiyuan shear zones, successively propagate to the eastern boundary of the model, where they generate extensional basins similar to the South China Sea and North China Rifts. They isolate two stable blocks (≈Sunda and South China). Remarkably, without changes in indentation rate, the activation of the northern shear zone triggers slip reversal on the southern one, as observed along Yunnan's Red River faults since the Miocene. On the west side of Sunda, the model generates faults comparable to the Sagaing fault and triangular basins similar to the Andaman and Mergui basins. Finally, the model suggests that crustal thickening across Tibet alternated with strike‐slip faulting. The main discrepancy between tectonic observations and model results is the striking difference in strike‐slip fault orientation, likely due to age‐dependent lithospheric strength. Key Points: Stepwise continental subduction and northward rise of Tibetan mountain ranges, and isolation of intervening captive basins Birth and propagation of lithospheric continental shear zones, coupled with far‐field opening of rifts and Oceanic basins Continental block extrusion and broad‐scale fault‐slip reversal